Crystal Structure of the Polyextremophilic α-Amylase AmyB from Halothermothrix orenii: Details of a Productive Enzyme-Substrate Complex and an N Domain with a Role in Binding Raw Starch - Tan, T.-C. (2014)
10.1016/j.jmb.2008.02.041